Maritime Sector As A Barometer Of Surabaya's Second Progress In Indonesia With The Spirit Of Building Starting From The Periphery - Prasutiyon, Hadi; Sutrisno, Sutrisno; Tambun, Robert (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
The importance of the socio-economic dimension of the utilization of marine potential in an area, with the existence of various regulations and technological developments, both regarding the technology of marine potential utilization tools and technology to develop and preserve the Marine potential itself, so that it can be utilized as much as possible for Prosperity. Contribution to fill the gap with socio-economic assessment of the utilization of the maritime sector of Surabaya city can be done by several steps, namely creating a” framework